Application of the Online Collaborative Learning Platform in Islamic Religious Education Learning: Its Impact on Academic Achievement and Student Learning Motivation - Sudadi Sudadi; Ahsan Hasbullah; Yusron Masduki; Nur Istiqomah; Syatria Adymas Pranajaya (Journal Neosantara Hybrid Learning, 2024)
The need to utilize technology to increase the effectiveness of Islamic learning, especially in achieving academic goals and strengthening student learning motivation continues to increase and develop. Therefore, an online collaborative learning platform is implemented in learning so that the learning process continues to move forward. The aim of this research is to evaluate the impact of using an online collaborative learning platform on students' academic achievement and learning motivation in the context of Islamic Religious Education learning. The research method used is a quantitative approach. Academic achievement data is collected through periodic tests and assessments, while learning motivation data is collected through previously validated questionnaires. Data analysis was carried out using appropriate statistical techniques. The research results show that the application of the online collaborative learning platform has a significant positive impact on students' academic achievement and learning motivation in Islamic Religious Education learning. Students who use the online collaborative learning platform show better improvements in understanding Islamic religious concepts and academic achievement in general. In addition, they also show higher levels of learning motivation and more active participation in learning. The conclusion of this research explains that the integration of online collaborative learning platforms in Islamic Religious Education learning has a positive impact on students, especially on students' academic achievement and learning motivation. This shows that the use of technology in the context of the Islamic religion can be an effective means of improving the quality of learning. Therefore, this research provides an important contribution to understanding the potential of technology in increasing the effectiveness of Islamic religious learning and emphasizes the importance of technology adoption in the context of Islamic religious education